Sifat mekanikal saduran epoksi mengandungi abu buangan industri - Nursyahirah Mohd Safie; Nor Yuliana Yuhana; Zakaria Man (Penerbit Universiti Kebangsaan Malaysia, 2018)
Organic epoxy coating was the primary focus of this study because of its thermosetting characteristics, high durability of adhesion to the substrate, stable structure, chemical resistance and economical cost. However, epoxy coating has several disadvantages in that it is easily cracked, brittle and sensitive to climate change due to its ability to easily absorb water. Humidity can weaken the structure of the coating. To resolve this issue, fly ash is added as reinforcement to the structure of the epoxy. Fly ash is a material that can improve the mechanical strength and durability of a coating. However, the optimum mass of fly ash in the epoxy should be studied carefully to produce an epoxy coating that is strong, stable and that does not easily absorb water. Therefore, this study was performed to synthesize epoxy resin with fly ash as filler, as well as to analyse the impact of fly ash on the properties of the epoxy coating through hardness strength tests. The characteristics of the epoxy resin with fly ash (MFA and OFA) and without fly ash (RE) were analysed by thermogravimetric analysis (TGA), Fourier-transform infrared spectroscopy (FTIR), and density and particle size analysis. Based on the FTIR analysis, fly ash does not change the structure of the functional groups in the epoxy. For the TGA analysis, the onset of degradation for MFA and OFA started to occur at 346 ± 1°C. The addition of 5% fly ash increased the hardness of the epoxy by up to 13% compared to the unmodified epoxy. Epoxy coatings can be improved in terms of their hardness and degradation time by the addition of fly ash as filler.